Rotifers from a humic coastal lagoon of Rio de Janeiro State, Brazil - Branco, Christina W. C. (2005)
A four-year study of species composition of the zooplankton community was conducted at Lagoa Comprida, a Brazilian coastal lagoon. Forty-two species of rotifers were recorded and iIIustrated. Ali rotifer species, except Lecane boettgeri Koste, 1986 and Macrochaetus kostei, José de Paggi, Branco & Kozlowsky-Suzuki, 2000, have already been found in other areas of Brazil. Some factors, which probably favored the dominant richness and density of rotifers in the zooplankton community, are discussed. Keywords: Rotifer assemblage, zooplankton, humic coastal lagoon, Comprida Lagoon, Neotropics, Hexanhra longicornicula